Recall dan Precision pada Online Public Access Catalog (OPAC) Dinas Arsip dan Perpustakaan Kota Bandung - Didik Prata Wijaya; Letizia Dwi Murti; Mochamad Reinnal Rachman (Perpustakaan Nasional RI, 2022)
Disarpus Bandung is a technical institution that has the task and function of developing the habit of reading fondness through library empowerment. The role of the Online Public Access Catalog (OPAC) as an information retrieval system is very supportive as a means or facilities to improve services to the community, especially in the field of libraries in the city of Bandung. This study aims to determine (1) How is recall and precision in the OPAC of the Disarpus Bandung. (2) effectiveness of OPAC as an information retrieval system in the city of Bandung. The data collection method used is by conducting keyword searches on the OPAC of the Disarpus Bandung through the website page http://layanan.dispusip.bandung.go.id/inlislite3/opac/. These 10 keywords were the most searched or searched by library users in March 2022 in Disarpus Bandung. Every keyword used in the search process, the result is a number of catalog data. The catalog data obtained is then analyzed and determined which data are relevant and irrelevant to the information needs sought based on the title, the subject of the book, and the availability of the collection. Then the recall and precision calculations will be carried out to determine the effectiveness of the INLISLite application retrieval. Based on the results of testing on the OPAC of the Disarpus Bandung with 10 keywords most frequently searched by users during March 2022, it can be concluded that the information retrieval system has been effective. This can be seen from the average recall value of 0.96 or 95.79% and the average precision value of 0.92 or 92.31%. Of the 10 keywords, namely nursing, human resources, communication, research methods, accounting, taxation, information systems, skills, parenting, and psychology, the keywords with the highest recall and precision values are research methods and parenting keywords, namely the recall value of 1 or 100% and a precision value of 1 or 100%. Meanwhile, the lowest recall and precision values are communication keywords, with a recall value of 0.90 or 90.34% and a precision value of 0.88 or 88.33%. Overall, the OPAC at the Disarpus Bandung has been effective as an information retrieval system.